Potential use of saline resources for biofuel production using halophytes and marine algae: prospects and pitfalls - Abideen, Zainul; Ansari, Raziuddin; Hasnain, Maria; Flowers, Timothy J.; Koyro, Hans-Werner; El-Keblawy, Ali; Abouleish, Mohamed; Khan, Muhammed Ajmal (Frontiers in Plant Science, 2023)
A food crisis, exacerbated by salinization and desertification of prime agricultural lands, has worsened due to edible plants' use for biofuel production. Consequently, there is growing interest in using non-food plants' biomass as a renewable energy source. Halophytes grown on marginal and degraded lands using saline water offer a supplemental potential for commercial-scale biofuel, especially bioethanol. At the same time, suitable microalgae strains cultured under similar conditions can be a particularly good source of biodiesel. However, determining the optimal conditions for producing biomass and end products is of primary importance. The use of algal biomass and halophytes has been reported for bioenergy production, but the actual efficiency of their mass-scale biomass production is still a concern for environmental protection. For halophytes, lack of seed supply impedes their use, as is variable seed germination and lack of knowledge of their propagation. The generation of biofuels from these feedstocks can have environmental impacts such as ecosystem alteration, the introduction of invasive species and transmissible plant diseases. At the same time, algal blooms can be toxic, and their nutrient releases cause land and aquatic systems eutrophication. Standardized conditions for increased biofuel production and their comparative evaluations are missing for both feedstocks. This review summaries the pitfalls and precautions for producing biomass in a way that limits environmental hazards and harms of coastal ecosystems. Some new algal and halophytic species with great potential as sources of bioenergy are highlighted in this review.